An Improved Water Budget for the El Yunque National Forest, Puerto Rico, as Determined by the Water Supply Stress Index Model. Issue 3 (27th March 2018) - Zhang, Liangxia; Sun, Ge; Cohen, Erika; McNulty, Steven G; Caldwell, Peter V; Krieger, Suzanne; Christian, Jason; Zhou, Decheng; Duan, Kai; Cepero-Pérez, Keren J
Abstract: Quantifying the forest water budget is fundamental to making science-based forest management decisions. This study aimed at developing an improved water budget for the El Yunque National Forest (ENF) in Puerto Rico, one of the wettest forests in the United States. We modified an existing monthly scale water balance model, Water Supply Stress Index (WaSSI), to reflect location watershed conditions, by incorporating a new empirical evapotranspiration (ET) equation derived from global eddy covariance data for rainforests. Modeling results indicated that the mean water yield was about 1795 mm yr -1 for the ENF region, representing approximately 63% of the annual precipitation. We found a wide range of the estimates for all key hydrological fluxes, particularly ET, among those reported in the literature. The large differences in both the magnitude and seasonality of fluxes are a result of differences in estimation methods and physical watershed boundaries used among these studies. The present modeling study that used the updated data products and modeling techniques provided an improved annual water budget with a smaller uncertainty compared to previous studies. Future studies should focus on quantifying water budgets, especially ET and precipitation, across a topographic gradient at a fine spatiotemporal scale.